JALAN ILLUMINASI DALAM MISTISISME HAZRAT INAYAT KHAN (1882 -1927) - Syaifan Nur; Asna Ulil Maizah (UIN Sunan Kalijaga Yogyakarta, 2019)
Mysticism comes from the Greek word mystikos, which means secret, hidden, dark or veiled in darkness. Also means silence or shut up, which is the basic word of mysterion in ancient Greek. Mysticism leads to the study of the esoteric side of the spiritual life of people who believe, have faith, and have religion. Mysticism seeks to uncover the deepest secrets in the spiritual life. One of the roads used is the path of illumination. Illumination is the key to enlightenment desired by every human being. In illumination, the goal of humans is to obtain inner solutions, and their birth, there are many forms or patterns that must be approached, seen and felt. Moreover, it must really enter into it, the estuary of the self-surrender to the worldliness that must be faced with realization, secret spirit, calm and deeds.The path of illumination requires an initiation process as a basis for stepping into the search for true nature. Initiation as a basic change in essential conditions; initiation as a reference for every human being to start, aiming for something that leads to a better direction. Actually and verbally, as a listener, imitator and speaker, the initiator is able to know step by step to make an inner journey to get enlightenment that is felt to be very influential in his life. One of the famous mystics who explore this issue is Hazrat Inayat Khan. The complex problem of human uncertainty is one of the driving forces that gave birth to the great thoughts of a Hazrat Inayat Khan. Hazrat Inayat Khan’s view holds that humans as God’s creatures in the world must return to their consciousness, function, purpose and existence in the essence of mankind itself properly and correctly. Life must be in harmony because all God’s creatures are the same creation from God Almighty. The ultimate goal is to get the true nature.